Teaching and Preaching: Missionary Education and Colonial Subjects in Italian Eritrea (1890–1935) - Tesfamariam, Temesgen (Journal of religion in Africa, 2023)
During European colonial times in Africa and elsewhere, missionary education was an integral part of the colonial instruments for political domination, economic exploitation, and cultural assimilation. This paper aims to investigate the process of making colonial subjects through missionary education that was mainly provided by Catholic and Evangelical mission schools during the Italian colonial period in Eritrea. The paper argues that the Catholic and Evangelical mission schools distinctively worked to achieve their separate objectives that can be explained as employment versus salvation, teaching versus preaching, flag versus Bible, and hands versus soul, respectively. While the Catholic mission school focused on training the hand in order to supply labour, the Evangelical mission school stressed harvesting the soul to cultivate a docile labour force. Despite their differences, the works of the Catholic and Evangelical mission schools placed much emphasis on and exerted much effort to producing a class of colonial subjects that could serve as brokers of power.